Vascular remodelling in idiopathic pulmonary fibrosis patients and its detrimental effect on lung physiology: potential role of endothelial-to-mesenchymal transition. Issue 1 (21st March 2022) - Gaikwad, Archana Vijay; Lu, Wenying; Dey, Surajit; Bhattarai, Prem; Chia, Collin; Larby, Josie; Haug, Greg; Myers, Stephen; Jaffar, Jade; Westall, Glen; Singhera, Gurpreet Kaur; Hackett, Tillie-Louise; et al.
Background: Idiopathic pulmonary fibrosis (IPF) is a progressive, irreversible fibrotic interstitial lung disease. We performed size-based quantitation of pulmonary arterial remodelling in IPF and examined the role of endothelial-to-mesenchymal transition (EndMT) and effects on lung physiology. Methods: Resected lung tissues from 11 normal controls (NCs), and 13 IPF patients were differentially stained using the Movat Pentachrome technique. Size-based classification for pulmonary arteries was conducted in NC and IPF tissues. For each pulmonary artery, arterial size, luminal diameter, thickness of the intima, media and adventitia, and elastin deposition were quantified using Image ProPlus7.0 software. In addition, immunohistochemical staining was performed for EndMT markers and collagen. Results: Large and medium-size arterial numbers were significantly reduced in IPF compared to NCs (p<0.0001). Intima thickness was highest in the arterial range of 200–399 μm and 600–1000 μm (p<0.0001), while medial and adventitial thickness was significant across 200–1000 μm (p<0.05) compared to NC. Medial thickness was found to significantly affect the diffusing capacity of the lungs for carbon monoxide ( D LCO ) (r=−0.8, p=0.01). Total arterial elastin in IPF was higher across all arterial ranges except 100–199 μm in IPF than in NC, with the greatest differences in 200–399 μm (p<0.001) and 600–1000 μm (p<0.001). Total elastin also negatively correlated with D LCO (r'=−0.63, p=0.04) in IPF. An increase in EndMT markers and collagen type I/ IV was observed. Conclusions: This is the first study demonstrating size-based differences in pulmonary arteries in IPF and its detrimental effect on lung physiology. The process of EndMT might be central to these vascular remodelling changes and could be a potential novel therapeutic target. Pulmonary arterial remodelling occurs in IPF patients, affects lung function and may exaggerate pulmonary hypertension. Endothelial-to-mesenchymal transition appears decisive with vascular changes and could be a novel therapeutic target for IPF. https://bit.ly/3GG3qBa